PENERAPAN AUDIT BASED RISK PADA PIUTANG MURABAHAH (STUDI PADA BANK MUAMALAT MALANG) - Dimas Mahardika Palupi; Eris Tri Kurniawati (Universitas Muhammadiyah Malang, 2018)
This study aims to analyze the implementation of audit-based risk on murabahah receivables in accordance with Indonesian bank regulations at Bank Muamalat Malang. The type of this research is descriptive qualitative with the technique used is an interview, observation, and documentation. Researchers used six risk control elements in accordance with control objectives. The result of the analysis at Bank Muamalat Malang shows that risk control is quite good. the implementation of effective risk management is good enough. The scope of risk management performed by the Bank is good enough. The risk rating for prioritizing the mitigation is also good. Practice with the principles of sharia and not contrary to the MUI fatwa is good. Implementation of risk management in Syariah business unit does not exist because in Bank Muamalat Malang there is no unit of sharia business. The rules of delivery on a quarterly basis to BI have also been disputed.